2022
DOI: 10.3390/brainsci12111532
|View full text |Cite
|
Sign up to set email alerts
|

Neck Muscle Vibration Alters Upper Limb Proprioception as Demonstrated by Changes in Accuracy and Precision during an Elbow Repositioning Task

Abstract: Upper limb control depends on accurate internal models of limb position relative to the head and neck, accurate sensory inputs, and accurate cortical processing. Transient alterations in neck afferent feedback induced by muscle vibration may impact upper limb proprioception. This research aimed to determine the effects of neck muscle vibration on upper limb proprioception using a novel elbow repositioning task (ERT). 26 right-handed participants aged 22.21 ± 2.64 performed the ERT consisting of three target an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Although the significance level ( p = 0.035) of this result is just below 0.05, its power is very high (almost one) and supports its reliability. The larger pointing bias in CD patients suggested by the present study, cannot arise from a proprioceptive disruption related to the abnormal neck input ( Tabbert et al, 2022 ), since it was observed only for a specific pointing direction (left targets), while a difficulty in arm control should be evident in all the sectors of the workspace. Moreover it was independent upon the dystonia severity, as well as upon the direction of head rotation/neck hypertonus.…”
Section: Discussionmentioning
confidence: 44%
See 3 more Smart Citations
“…Although the significance level ( p = 0.035) of this result is just below 0.05, its power is very high (almost one) and supports its reliability. The larger pointing bias in CD patients suggested by the present study, cannot arise from a proprioceptive disruption related to the abnormal neck input ( Tabbert et al, 2022 ), since it was observed only for a specific pointing direction (left targets), while a difficulty in arm control should be evident in all the sectors of the workspace. Moreover it was independent upon the dystonia severity, as well as upon the direction of head rotation/neck hypertonus.…”
Section: Discussionmentioning
confidence: 44%
“…It is possible, therefore, that a similar phenomenon occurs in CD patients, making movement planning and execution more difficult. Finally it has to be mentioned that an altered neck proprioceptive input may get worse the limb position sense ( Tabbert et al, 2022 ), possibly leading to a movement impairment which could account for the increase in DEV observed in CD patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It also contributes to the control of balance, postural control, head position and fine motor skills in tasks that require precise movements of the neck and upper body. 9,10,37,38 Therefore, changes in head and neck position may affect the perceived position of body parts relative to each other, the perception of the target position, and/ or the perception of body position by causing changes in proprioceptive afferent information. 13 Knox and Hodges 13 showed that changes in head and neck position in the absence of visual cues in healthy individuals affect the processing of afferent sensory inputs and may alter elbow proprioception.…”
Section: Discussionmentioning
confidence: 99%